Linearly ordered compact sets and co-Namioka spaces - Mykhailyuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
It is proved that for any Baire space X, linearly ordered compact Y, and separately continuous mapping f: X × Y → R, there exists a G_δ-set A X dense in X and such that f is jointly continuous at every point of the set A × Y, i.e., any linearly ordered compact is a co-Namioka space.